Elderly donor liver grafts are not associated with a higher incidence of biliary complications after liver transplantation: results of a national multicenter study. (17th June 2015) - Westerkamp, Andrie C.; Korkmaz, Kerem S.; Bottema, Jan T.; Ringers, Jan; Polak, Wojciech G.; van den Berg, Aad; van Hoek, Bart; Metselaar, Herold J.; Porte, Robert J.
Abstract: Background: Liver transplantation with livers grafts from elderly donors has been associated with a higher risk of biliary complications. The aim of this study was to examine whether our national protocol could contribute to a lower incidence of biliary complications. Methods: All adult recipients in the Netherlands transplanted with a liver from an elderly donor (≥65 yrs; n = 68) in the period January 2000–July 2011 were matched with recipients of a liver from a donor <65 yr (n = 136). Outcome parameters were 90‐d, one‐yr, and three‐yr patient/graft survival rates, biliary complications (non‐anastomotic stricture, anastomotic stricture, biliary leakage, and post‐transplant cholangitis), and postoperative hepatic ischemic injury serum markers (AST/ALT). Results: The median cold ischemia time (CIT) was 7:25 (h:min) in the group recipients of an elderly donor liver graft. Ninety‐day, one‐yr, and three‐yr patient/graft survival rates were similar between the group with an elderly donor liver and their younger controls. Moreover, no differences were found in the incidence of biliary complications and postoperative levels of AST/ALT between the two groups. Conclusion: Transplantation of livers from elderly donors (≥65 yr) is not associated with a higher incidence of biliary complications, in a national policy wherein the CIT is kept short.